Functional identification of APIP as human mtnB, a key enzyme in the methionine salvage pathway. - Camille Mary (Public Library of Science (PLoS), 2012)
The methionine salvage pathway is widely distributed among some eubacteria, yeast, plants and animals and recycles the sulfur-containing metabolite 5-methylthioadenosine (MTA) to methionine. In eukaryotic cells, the methionine salvage pathway takes place in the cytosol and usually involves six enzymatic activities: MTA phosphorylase (MTAP, EC 2.4.2.28), 5'-methylthioribose-1-phosphate isomerase (mtnA, EC 5.3.1.23), 5'-methylthioribulose-1-phosphate dehydratase (mtnB, EC: 4.2.1.109), 2,3-dioxomethiopentane-1-phosphate enolase/phosphatase (mtnC, EC 3.1.3.77), aci-reductone dioxygenase (mtnD, EC 1.13.11.54) and 4-methylthio-2-oxo-butanoate (MTOB) transaminase (EC 2.6.1.-). The aim of this study was to complete the available information on the methionine salvage pathway in human by identifying the enzyme responsible for the dehydratase step. Using a bioinformatics approach, we propose that a protein called APIP could perform this role. The involvement of this protein in the methionine salvage pathway was investigated directly in HeLa cells by transient and stable short hairpin RNA interference. We show that APIP depletion specifically impaired the capacity of cells to grow in media where methionine is replaced by MTA. Using a Shigella mutant auxotroph for methionine, we confirm that the knockdown of APIP specifically affects the recycling of methionine. We also show that mutation of three potential phosphorylation sites does not affect APIP activity whereas mutation of the potential zinc binding site completely abrogates it. Finally, we show that the N-terminal region of APIP that is missing in the short isoform is required for activity. Together, these results confirm the involvement of APIP in the methionine salvage pathway, which plays a key role in many biological functions like cancer, apoptosis, microbial proliferation and inflammation.